The Employment of Antecedent Strategy for Managing Behavior Challenges in EFL Classroom - Nyoman Gita Pariska (Indonesian Journal Of Educational Research and Review, 2022)
Antecedent strategy as a part of the evidence-based practice is obtained through the process of students interfering behaviour analysis. This part of evidence-based practice which also named as antecedent-based intervention has a purpose to help the teachers in managing student disruptive behavior as one of the biggest challenges in classroom management by making a significant change to the learning environment which trigger the problem behavior and expounding the behaviors that should be done by the students. The antecedent strategy is very helpful for the teacher in managing students' disruptive behavior as one of the biggest challenges in EFL classroom management. Therefore, this study aims to analyze the employment of antecedent strategy for managing behavioral challenges in EFL classroom management. The method used in this study was library research in which the data were collected through a reading process of some library sources then analyzed by integrating the obtained information and the researcher's idea to answer the purpose of this research in finding section and draw the conclusion. The findings of this study revealed that in employing the antecedent strategy in a classroom, there are three major steps that the teacher needs to follow namely conducting a Functional Behavioral Assessment (FBA), clearly expounding the proper behavior, and effectively deciding preventive action.